Metallic 1T-TiS2 nanodots anchored on a 2D graphitic C3N4 nanosheet nanostructure with high electron transfer capability for enhanced photocatalytic performance. Issue 87 (5th December 2017) - Liu, Yang; She, Xiaojie; Zhang, Xiaoni; Liang, Chenglu; Wu, Jingjie; Yu, Peng; Nakanishi, Yusuke; Xie, Banghu; Xu, Hui; Ajayan, Pulickel M.; Yang, Wei
Abstract : The introduction of metallic TiS2 nanodots in 2D-C3 N4 nanosheets improved the photocatalytic activity due to the suppression of e–h recombination. Abstract : Photocatalysis is one of the most promising technologies for solar energy conversion. With the development of photocatalysis technology, the creation of low-dimensional structure photocatalysts with improved properties becomes more and more important. Metallic 1T-TiS2 nanodots with a low-dimensional structure were introduced into environmentally friendly two-dimensional g-C3 N4 (2D-C3 N4 ) nanosheets by a solvothermal method. It was found that the ultrathin TiS2 nanodots were uniformly anchored on the surface of the 2D-C3 N4 . The effective suppression of electron–hole recombination was realized due to the addition of the intrinsic metallic property of 1T-TiS2 in the prepared nanocomposite. The 5 wt% TiS2 /2D-C3 N4 nanocomposite exhibited the best photocatalytic performance and the degradation rate towards RhB was ca. 95% in 70 min, which showed an improvement of ca. 30% in comparison with 2D-C3 N4 . The results indicate that the obtained TiS2 /2D-C3 N4 nanocomposite is a promising photocatalyst for practical applications.